The Geologically Supervised Spectral Investigation as a Key Methodology for Identifying Volcanically Active Areas on Venus. Issue 7 (22nd July 2021) - D'Incecco, P.; Filiberto, J.; López, I.; Gorinov, D. A.; Komatsu, G.; Martynov, A.; Pisarenko, P.
Abstract: Combining geologic mapping and stratigraphic reconstruction of lava flows at Sapas, Maat and Ozza Montes, three potentially young volcanic structures of Atla Regio on Venus, with analysis of the spectral signature (radar emissivity anomalies) characterizing each mapped flow, Brossier et al. (2021, https://doi.org/10.1029/2020je006722 ), conclude that some of the lava flows at Maat Mons may be geologically recent (∼25 Ma) (Smrekar et al., 2010, https://doi.org/10.1126/science.1186785 ; D'Incecco et al., 2017, https://doi.org/10.1016/j.pss.2016.12.002 ; Zolotov, 2018, https://doi.org/10.1515/rmg.2018.84.10 ; Brossier et al., 2020, https://doi.org/10.1016/j.icarus.2020.113693, 2021, https://doi.org/10.1029/2020je006722 ). The lava flows of Sapas and Ozza Montes are consistent with weathered lava flows forming chlorapatite and some perovskite oxides. We discuss the reasons why, besides the importance of the results they obtained, the methodology they used can be very valuable for future investigations with higher resolution datasets. Plain Language Summary: Combining geologic mapping and stratigraphic reconstruction of lava flows at Sapas, Maat and Ozza Montes, three potentially young volcanic structures of Atla Regio on Venus, with analysis of the spectral signature (radar emissivity anomalies) characterizing each mapped flow, Brossier et al. (2021), https://doi.org/10.1029/2020je006722 conclude that some of the lava flows at Maat Mons may be geologically recent (∼25 Ma). The lava flows of Sapas and Ozza Montes are more consistent with weathered lava flows forming chlorapatite and some perovskite oxides. We discuss the reasons why, besides the importance of the results they obtained, the methodology they used can be very valuable for future investigations with higher resolution datasets. Key Points: The geologically supervised spectral investigation has been used to analyze three volcanic structures of Venus The authors conclude that some lava flows at Maat Mons may be as recent as ∼25 Ma In future missions, these techniques can be used to provide new elements in the debate on the style of resurfacing on Venus